Identifikasi sifat fisis batuan reservoir karbonat menggunakan inverse acoustic impedance (AI) model sparse spike pada lapangan “ABDUH” formasi Kujung Cekungan Jawa Timur Utara - Saad Abdurrahman; Udi Harmoko; Agung Ardiyanto (Youngster Physics Journal, 2017)
Physical rocks properties identification on "ABDUH" field, North East Java Basin has been done by acoustic impedance seismic inversion. The research aim conducted to predict the physical properties of rock by  acoustic impedance inversion value and the porosity distrubution by linier programming sparse spike. Sparse spike linear programming method assumes that a reflectifity regarded as the model a series of rarely spike and the big value deconvoluted with a new spike smaller than before maked it more accurated. This study used at single well and seismic 3D data post stack time migration is the area on research. Then with assumes a linear relationship between acoustic impedance and log porosity log based crossplot, obtained linear equation which was used to get the distribution of porosity from the distribution of acoustic impedance. Inversion results show the distribution of reefs on Kujung Reef formation has the porosity value 21-27% and the acoustic impedance vaue 17.000 to 28.000 ft/s.g/cc.Keywords: Acoustic Impedance, Kujung Reef, Porosity, Linier Programming Sparse Spike Inversion